Promoting professional development in medical education: perspectives from the Norwegian medical school in Tromsoe. Issue 1 (1st January 2018) - Hovdenak, Sylvi Stenersen; Wiese, Eline F.
ABSTRACT: In international research on medical education the concepts of professionalism and professional development have been increasingly focused. The article problematizes and discusses these concepts in relation to the Aristotelian concepts of episteme, techne and phronesis. Phronesis as a form of knowledge is of fundamental importance regarding professionalism and professional development, and can be regarded as a response to an instrumentalist understanding of medical education. The article reports from an ongoing qualitative study following the revision of the study programme in medicine at the Medical School University of Tromsoe, The Arctic University of Norway. In the renewed programme the concept of phronesis is paid attention to, and the article discusses how phronesis is focused on different learning arenas. The data presented builds on the students' perspectives on phronesis as a form of knowledge in medical education.